1996
DOI: 10.1073/pnas.93.9.4006
|View full text |Cite
|
Sign up to set email alerts
|

cemA homologue essential to CO2 transport in the cyanobacterium Synechocystis PCC6803.

Abstract: We have isolated mutants of Synechocystis PCC6803 that grew very slowly in a low-sodium medium, which is unfavorable for HCO3 transport, and examined two of these mutants (SC1 and SC2) for their ability to take up CO2 and HCO in the light. The COz transport activity of SC1 and SC2 was much lower than that of the wild type (WT), (18) supplemented with 20 mM Hepes-KOH buffer (KOH added to pH 8.0) during aeration with 3% vol/vol CO2 in air. Low-sodium medium was prepared by adding NaCl (final concentration, 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…However, no data are available on the function of the cemA gene product (CemA). Both CemA and CotA contain four membrane-spanning domains, and their amino acid sequences are highly conserved, especially in the C-terminal regions (4). These results suggested that these chloroplast and cyanobacterial gene products may have a similar function, and elucidation of the role of CotA is an important step not only in the study of cyanobacterial physiology but also in clarifying the role of CemA in higher plants.…”
mentioning
confidence: 86%
“…However, no data are available on the function of the cemA gene product (CemA). Both CemA and CotA contain four membrane-spanning domains, and their amino acid sequences are highly conserved, especially in the C-terminal regions (4). These results suggested that these chloroplast and cyanobacterial gene products may have a similar function, and elucidation of the role of CotA is an important step not only in the study of cyanobacterial physiology but also in clarifying the role of CemA in higher plants.…”
mentioning
confidence: 86%
“…There was no Shine-Dalgarno (26) Comparison of CotA and CemA sequences. As reported in a previous paper (6), the amino acid sequence deduced from the nucleotide sequence of the cotA gene of Synechocystis sp. strain PCC6803 showed significant similarity to the sequences of cemA gene products of various plants (3,15,24,27,30).…”
Section: Resultsmentioning
confidence: 96%
“…When the first ATG was postulated as the initiation codon, the gene product was a 51-kDa protein of 440 amino acids. We concluded in a previous paper that the translation started from the second ATG codon, giving a gene product of 29 kDa (247 amino acids), close in size to CemA of higher plant chloroplasts (6,24). However, a preliminary experiment to identify the gene product suggested that it may be much larger.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of CCMs results in the energy-dependent transport of both HCO 3 Ϫ and CO 2 across the cytoplasmic membrane and the formation of a large intracellular pool of C i which is used during photosynthesis. Along with as yet unidentified CO 2 /HCO 3 Ϫ transporter proteins and energization components involving NADP(H) dehydrogenasedependent photosystem I electron flow (14,19), a proteinencapsulated aggregate of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) called a "carboxysome" is an integral part of a cyanobacterial CCM. It is hypothesized that associated with the cyanobacterial carboxysome is the ␤-type CA, a product of the icfA (also designated ccaA) gene (8,20,27).…”
mentioning
confidence: 99%